Teor de lignina em sementes e legumes de soja: relação com a deterioração por umidade, deiscência e análise da expressão gênica - Madureira, Alana (2021)
The soybean crop (Glycine max (L.) Merril) has great economic importance for Brazil. The occurrence of unfavorable climatic conditions in the pre-harvest of soybean seeds, after physiological maturity, can cause damage and negatively affect seed quality. The objective of this work was to evaluate the physiological quality of seeds of different soybean cultivars with different lignin content in the pod and seed coat submitted to wheathering deterioration in pre-harvest. In addition, four cultivars contrasting to the wheathering deterioration tolerance were selected to determine the relative expression of key genes involved in the lignin biosynthesis pathway, pectin deposition and genes involved in resistance to pod dehiscence. Experiments were conducted using 17 soybean cultivars. In phenological stage R5.2, the pods were collected and to relative gene expression analyzes. The target genes of the lignin biosynthesis pathway (F5H, SCPL, CAD, POD, ALDH, COMT, CCR and CSE), pectin deposition (PE) and transcription factors related to pod dehiscence (SHAT1-5 and NST1A). In R8, a rain simulation was carried out during three consecutive days , having accumulated 150 mm. After full maturation, the analysis of germination, tetrazolium, lignin content in the pod and seed coat was performed. The relative expression was performed using the 2-ΔΔct method, with the endogenous β actin gene as reference and the cultivar BMX ZEUS as the calibrator sample. Within the set of 17 cultivars, it was possible to classify the cultivars with the highest lignin content, where the cultivar BRSMG715A with black seed coat can be highlighted, followed by the cultivar BRSMG 800A with the brown seed coat and the cultivar with yellow seed coat being the cultivar BRS 388 RR, in relation to the cultivars with the highest lignin content in pod, the cultivars M8210, BRS 388RR and BRS Jiripoca can be highlighted. Regarding the physiological quality of seed evaluations through tetrazolium analysis, the cultivars with the greatest damage by weathering were BMX ZEUS and BRS 511 and with the least damage were BRS 388RR and BRS Jiripoca, and the cultivars that showed the greatest damage to vigor and viability were the cultivars BMX ZEUS and BRS 511. The cultivars with the lowest physiological seed quality were those with the lowest lignin content in the seed coat and pod. Regarding the results of relative expression, it was observed that cultivars with higher lignin content had higher relative expression, and the other group with lower relative expression compared to BMX ZEUS cultivar, consequently the genes of the biosynthesis pathway of lignin and the dehiscence resistance gene SHAT1-5 were more expressed in cultivar BRS 388RR with higher lignin content, and less expressed in cultivar BRS 511 with lower lignin content.